Respostas agronômicas de capim-ipyporã sob estratégias de fornecimento de nitrogênio : fertilizante mineral, inoculante bacteriano e consórcio com amendoim forrageiro - Bourscheidt, Maira Laís Both (2018)
Nitrogen (N) is an essential element in pasture production. Some alternatives for the supply of N are nitrogen fertilization, the use of a consortium with forage legumes and the use of inoculant with diazotrophic bacteria in grasses. The objective was to evaluate agronomic responses of ipyporã grass (Brachiaria spp.) under nitrogen supply strategies. The experiment was carried out at Embrapa Agrossilvipastoril in Sinop - MT and followed a randomized complete block design with 6 treatments and 3 replicates: 1. Pastures of ipyporã grass without nitrogen fertilization (control); 2. fertilizers with 80 kg N.ha-1 .ano-1 (N); 3. inoculated with Azospirillum brasilense (i); 4. fertilizers with 80 kg.ha-1 of N + inoculant (N + i); 5. in consortium with forage peanuts (Arachis pintoi cv. Mandobi) (C); 6. in consortium with forage peanut + inoculant (C + i). The experimental period was from March 21, 2015 to March 21, 2017. The pastures were harvested when reached a height of 25 cm, leaving a 12 cm of stubble and also in representative cycles in the middle of the seasons (spring/15, summer/16, spring/16 and summer/17), from 25 to 12 cm for quantification of forage mass (FM) above the stubble and the stubble level to soil for quantification of stubble, and biomass being the sum of both. At the end of the experimental period, samples were also collected to quantify stubble and root mass. The highest accumulations (FA), forage accumulation rates (FAR), FM and leaf mass were observed in the N and C + i strategy. Larger biomass was recorded in pastures with N, N + i and C + i and for stubble s in N and N + i strategies, especially in seasons with higher rainfall. Stem and dead material above the stubble were influenced only by the seasons, with more masses and proportions in the summers for stem and smaller in the summer/17 for dead material. The highest index of destructive leaf area index (DLAI) was observed in pastures with N and the highest DLAI were recorded in the summers, while for light interception (LI), pastures with N and N + i intercepted more light, especially in summer/17. In the structural characterization of the stubble, morphological components (leaf, stem and dead material), destructive leaf area index (DLAI) and light interception (IL) were positively influenced, in a general way, by nitrogen supply strategies, mainly in pastures with N and N + i by greater water xii availability. This same pattern of response was observed for the qualitative indicators, crude protein (CP) and neutral detergent insoluble fiber (NDF), and for the physiological variables stomatal conductance (sc), water use efficiency (WUE) and total chlorophyll. For all nitrogenous strategies, higher root mass was observed when compared to the control, as well as higher stubble mass, especially with N. The mineral fertilization and the C + i strategies increased the N concentration in the roots, and the N stock was higher with the mineral fertilization. It is concluded that ipyporã grass is responsive to N supply strategies, with relative gains between 14 and 42% for FA and between 6 and 26% in biomass, with better responses when submitted to the N and C + i strategy.